The Questioning of the Concept of Masculinity in Joyce Lebras The Scent of Sake - Sindhy Sintya Mianani; Elisa Dwi Wardani (Universitas Sanata Dharma, 2018)
Gender is the social construction of elaborating sex, which is supposed to be distinguished from the biological categories of being male or female. Gender is said to be a very complex phenomenon and one has to acquire it through the process of socialization. Sex itself determines gender, while gender determines gender roles, whether it is masculinity or femininity. This study discusses Joyce Lebras The Scent of Sake as a novel which portrays a violation to the concept of masculinity recognized in Japanese male gender roles, or also known as daikokubashira, through the analysis of its male character, Jihei. The discussion consists of the analysis of how Jihei is depicted as an unmasculine man in the novel. Then, followed by the discussion on the reason why Jiheis unmasculine characteristics are considered as a form of violation to the concept of masculinity recognized in daikokubashira.The results of this study shows that Jihei is depicted as a man whose characteristics reject the masculine qualities expected by society. Thus, they are also said as questioning the concept of masculinity recognized in daikokubashira. Hence, it can be said that Joyce Lebras The Scent of Sake portrays and encourages masculinity as a mandatory characteristic which is supposed to be possessed by men, especially in patriarchal culture, but it also counts as a double-edged sword for them.Keywords: questioning, masculinity, daikokubashira